Polarização de spin em heteroestruturas semicondutoras contendo pontos quânticos de InAs - Santos, Ednilson Carlos dos (Universidade Federal de São Carlos, 2010)
In this work, we have studied spin polarization of carriers in a resonant tunneling diode GaAs/AlGaAs with InAs quantum dots in the center of the quantum well. We have observed that the photoluminescence of quantum dots depends on applied voltage and light intensity. Our results were explained by the capture of minority carriers (holes) to quantum dot energy levels in the resonant conditions. We have also studied the polarized resolved photoluminescence under magnetic field applied parallel to the tunnel current. We have observed that the degree of circular polarization is voltage-dependent under low voltage and laser intensity condition. We have also observed that the degree of polarization of quantum dots tends to zero for high applied voltages. Our results show that the circular polarization depends on the injection and capture of holes by quantum dots. Finally, we observed that the circular polarization from quantum dots can be voltage and light-controlled and could be interesting for the developing of new spintronics devices.
Keywords: Semicondutividade e semicondutores; Spintrônica; Tunelamento (Física); Fotoluminescência; Diodos; Pontos quânticos; Spintronic; Tunneling; Photoluminescense; Quantum dots; Diode; CIENCIAS EXATAS E DA TERRA::FISICA